2013
DOI: 10.1098/rsob.120185
|View full text |Cite
|
Sign up to set email alerts
|

Aurora at the pole and equator: overlapping functions of Aurora kinases in the mitotic spindle

Abstract: The correct assembly and timely disassembly of the mitotic spindle is crucial for the propagation of the genome during cell division. Aurora kinases play a central role in orchestrating bipolar spindle establishment, chromosome alignment and segregation. In most eukaryotes, ranging from amoebas to humans, Aurora activity appears to be required both at the spindle pole and the kinetochore, and these activities are often split between two different Aurora paralogues, termed Aurora A and B. Polar and equatorial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 140 publications
(205 reference statements)
4
113
0
Order By: Relevance
“…Aurora kinase A encodes a protein that localizes to the spindle poles, contributes to separation and maturation of the centrosomes during mitosis, plays a pivotal role in G2/M cell cycle progression and is frequently amplified in several types of cancer. 71,72 Aurora kinase B encodes a chromosomal passenger protein that is required for proper mitosis and cytokinesis. 73 Here, we have demonstrated that glioma cells treated with cucurbitacin develop spindle abnormalities and multinucleated cells at a high frequency, consistent with the results of previous reports on Aurora kinase A, Aurora kinase B and survivin inhibition in a variety of experimental systems.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora kinase A encodes a protein that localizes to the spindle poles, contributes to separation and maturation of the centrosomes during mitosis, plays a pivotal role in G2/M cell cycle progression and is frequently amplified in several types of cancer. 71,72 Aurora kinase B encodes a chromosomal passenger protein that is required for proper mitosis and cytokinesis. 73 Here, we have demonstrated that glioma cells treated with cucurbitacin develop spindle abnormalities and multinucleated cells at a high frequency, consistent with the results of previous reports on Aurora kinase A, Aurora kinase B and survivin inhibition in a variety of experimental systems.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Mad1 levels were also reduced on polar chromosomes after inhibition of Aurora A kinase, indicating a role of Aurora A in the spatial regulation of kinetochore-microtubule attachments near the spindle poles. Indeed, Aurora A had been previously implicated in the stabilization of kinetochore-microtubule attachments, 49,50 which might be explained by the fact that Aurora A shares 70% identity of its catalytical domain with Aurora B 51 and that both kinases recognize almost identical consensus target motifs. 52 Thus, Aurora A and Aurora B might have overlapping functions in the correction of kinetochoremicrotubule attachments that are spatially regulated by their different localization (Aurora A being placed at the centrosomes and Aurora B at the centromeres), which is defined by their different binding partners.…”
Section: Dynein Prevents Prematurementioning
confidence: 99%
“…52 Thus, Aurora A and Aurora B might have overlapping functions in the correction of kinetochoremicrotubule attachments that are spatially regulated by their different localization (Aurora A being placed at the centrosomes and Aurora B at the centromeres), which is defined by their different binding partners. 51 Additionally, Aurora A might play other important roles in chromosome congression by regulating proteins directly involved in this process. 53,54 Two recent studies further confirmed our observation about the role of Aurora A in error correction near the poles in mitosis and also in meiosis I. Ye and colleagues 41 demonstrated the existence of an Aurora A activity gradient centered on the spindle poles in Drosophila S2 cells using a Fluorescence Resonance Energy Transfer sensor bound to microtubules that was Figure 1.…”
Section: Dynein Prevents Prematurementioning
confidence: 99%
“…Aurora kinases exert multiple roles in diverse cell cycle-related processes by phosphorylating a wide variety of substrates (Biggins and Murray, 2001;Carmena et al, 2009;Fu et al, 2009;Hans et al, 2009;Van Damme et al, 2011;Petrovská et al, 2012;Hochegger et al, 2013;Demidov et al, 2014;Goldenson and Crispino, 2015;Weimer et al, 2015). However, to date, only histone H3 (Hsu et al, 2000) and TPX2 have been reported as alpha Aurora substrates in plants (Demidov et al, 2005;Tomaštíková et al, 2015).…”
Section: Discussionmentioning
confidence: 99%